1990
DOI: 10.1677/joe.0.1270363
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor in small antral ovarian follicles of pregnant women

Abstract: Levels of epidermal growth factor (EGF) and steroids were measured by radioimmunoassay in follicular fluid (FF) aspirated from 114 small antral follicles with diameters from 1 to 6 mm and in serum from 19 women undergoing Caesarean section at term. Concentrations of EGF in FF were inversely and significantly correlated to follicular size, being 4.7 +/- 0.4 (mean +/- S.E.M.) nmol/l in follicles of 1-2 mm in diameter and declining to 2.2 +/- 0.2 and 1.4 +/- 0.2 nmol/l in follicles of 3-4 mm and 5-6 mm in diamete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…Preliminary studies were performed to determine the FSH and EGF concentrations and the time needed to observe an effect on StAR mRNA accumulation. Follicular fluid concentrations of EGF in different species have been reported to range from the low picograms per milliliter up to approximately 30 ng/ml [36,37]. Our preliminary studies revealed 10 ng/ml EGF was the lowest dose exhibiting statistically significant inhibition of StAR mRNA in combination with FSH and it was also a maximal dose.…”
Section: Resultsmentioning
confidence: 62%
“…Preliminary studies were performed to determine the FSH and EGF concentrations and the time needed to observe an effect on StAR mRNA accumulation. Follicular fluid concentrations of EGF in different species have been reported to range from the low picograms per milliliter up to approximately 30 ng/ml [36,37]. Our preliminary studies revealed 10 ng/ml EGF was the lowest dose exhibiting statistically significant inhibition of StAR mRNA in combination with FSH and it was also a maximal dose.…”
Section: Resultsmentioning
confidence: 62%
“…An EGF-like substance has been shown to be secreted by rat ovarian thecal/ interstitial cells [13], and EGF has also been found in both pig (13.6 ng/ml) [6] and human (1.56-3.3 ng/ml) [29] follicular fluids. Other reports [7,30] have shown follicular fluid levels of EGF in women to range from 0.60 to 31.3 ng/ml. Additionally, EGF has been found to stimulate proliferative effects (increased [ 3 H]thymidine incorporation) in granulosa cells while attenuating FSH-induced differentiating functions; i.e., EGF decreases estrogen secretion by granulosa cells and inhibits the increase in FSH-induced LH receptors [11].…”
Section: Discussionmentioning
confidence: 85%
“…Serum is a highly complex combination of components including proteins, fatty acids, vitamins, trace elements, hormones, and growth factors. Thus, EGF in serum [6,7,45] is possibly one of the undetermined components contributing to enhanced oocyte maturation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among various polypeptide growth factors, epidermal growth factor (EGF) is detected in porcine [1] and human follicular fluid [2] and shown to be synthesized by thecal/ interstitial cells [3]. In addition, granulosa cells possess the receptor for EGF in several species [4][5][6][7].…”
mentioning
confidence: 99%